Justice, Education, and the World of Today Philosophical Investigations - Bostad, Inga; Papastephanou, Marianna; Strand, Torill (Routledge International Studies in the Philosophy of Education, 2023)
This edited book challenges the limits of current educational philosophical discourse and argues for a restored normativisation of education through a powerful notion of justice. Moving beyond conventional paradigms of how justice and education relate, the book rethinks the promotion of justice in, for, and through education in its current state. Chapters combine international and diverse philosophical perspectives with a focus on contemporary issues, such as climate change, the COVID-19 pandemic, racism, and migrant crises. Divided into three distinct parts, the book explores the ontological and socio-political grounds underlying our notions of education and justice, and offers self-reflective meta-critique on education philosophers' tendency of promoting and upholding orthodox visions and missions. Ultimately, the book offers contemporary and innovative philosophical reflections on the link between justice and education, and enriches the discourse through a multi-perspectival and sensitive exploration of the topic. It will be of great interest to scholars, researchers, and postgraduate students in the fields of philosophy of education, education policy and politics, education studies, and social justice. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license. Funded by University of Oslo.